Cognitive behaviour therapy for people with intellectual disabilities : thinking creatively - Jahoda, Andrew; Kroese, Biza Stenfert, 1954-; Pert, Carol (Palgrave Macmillan, 2017)
This book examines the influence others have on the lives of people with intellectual disabilities and how this impacts on their psychological well-being. Based on the authors' clinical experiences of using cognitive behavioural therapy with people who have intellectual disabilities, it takes a social interactionist stance and positions their arguments in a theoretical and clinical context. The authors draw on their own experiences and several case studies to introduce novel approaches on how to adapt CBT assessment and treatment methods for one-to-one therapy and group interventions. They detail the challenges of adapting CBT to the needs of their clients and suggest innovative and practical solutions. This book will be of great interest to scholars of psychology and mental health as well as to therapists and clinicians in the field.